1992
DOI: 10.3758/bf03211697
|View full text |Cite
|
Sign up to set email alerts
|

Prime time: Fatigue and set effects in the perception of reversible figures

Abstract: Subjects viewed unambiguous versions of both stationary and rotating Necker cube illusions for varying durations prior to the presentation of the standard ambiguous figure. In each case, the subjects were more likely to report the ambiguous figure to be (1) in the same configuration as that ofthe preceding prime following briefpreexposure periods and (2) in the opposite configuration from that of the preceding prime following long preexposure periods. In addition, the number of reversals of the figure during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 31 publications
12
119
0
2
Order By: Relevance
“…In addition, it is known that briefly presenting an unambiguous version of a bistable figure prior to presenting the corresponding ambiguous figure can produce priming effects. In this regard, our results are consistent with the findings of Long et al (1992), who showed the effects of short, prior presentations of an unambiguous version of an ambiguous figure (previous experience or perceptual learning) on the response of observers.…”
Section: How Prior Experience Affected the Responsessupporting
confidence: 92%
“…In addition, it is known that briefly presenting an unambiguous version of a bistable figure prior to presenting the corresponding ambiguous figure can produce priming effects. In this regard, our results are consistent with the findings of Long et al (1992), who showed the effects of short, prior presentations of an unambiguous version of an ambiguous figure (previous experience or perceptual learning) on the response of observers.…”
Section: How Prior Experience Affected the Responsessupporting
confidence: 92%
“…Such a gamma-band mechanism is congruent with a bottom-up approach to the increase was not found. Since binding-related gamma explanation of reversible figures [21,29,35,43,72], since activity was found in a number of studies, the failure of the slowly decreasing alpha activity probably reflects a this activity in the present study may be due to the small passive and automatic process which is not represented in…”
Section: Oscillatory Activitymentioning
confidence: 61%
“…In particular, Long, Toppino, and Mondin (1992) had participants view unambiguous Necker cube figures for prime durations ranging from 1 to 150 s (ambiguity was removed by rotation and occlusion in separate conditions). For short prime durations, participants initially interpreted a subsequently presented ambiguous Necker cube in accord with the prime presentation, and for long prime durations the opposite was true.…”
Section: Perceptual Primingmentioning
confidence: 99%